HUBUNGAN TRAIT KEPRIBADIAN & STRATEGI COPING PADA PASIEN MULTIDRUGS-RESISTANT TUBERCULOSIS (MDR-TB) - Anne Desyana (MANASA, 2019)
The purpose of this research is to know the relationship between personality trait and copingstrategy among Multi drugs-Resistant (MDR TB) patient. There are 18 participants for thisresearch. Questionnaires were used in this research: DASS used to screen the patient level ofdepression, anxiety, and stress, NEO PI-R used to know their personality trait, and BRIEFCOPE used to know their strategy coping. The result showed that there is relationship betweenpersonality trait (neuroticism, extraversion, openness to experience, and agreeableness) andcoping strategy (venting, positive reframing, religion, humor, use of instrumental support,denial, self-distraction, self-blame). Domain extraversion is trait that has the most significantcorrelations with coping strategy. Based on the result, the institution has to cooperate withpsychologist in order to help patient reducing their tension during their medical treatmentprogram. This recommendation align with result of this research that show venting is the mostused coping strategy.Keyword: MDR TB, Coping strategy, Personality Trait